Effectiveness of whole-exome sequencing for the identification of causal mutations in patients with suspected inherited ocular diseases - Vianey Ordoñez-Labastida; Luis Montes-Almanza; Froylan García-Martínez; Juan C. Zenteno (Permanyer, 2022)
Background: Genetic eye disorders, affecting around one in 1000 people, encompass a diverse group of diseases causing severe visual deficiency. The recent adoption of next-generation sequencing techniques, including whole-exome sequencing (WES), in medicine has greatly enhanced diagnostic rates of genetically heterogeneous diseases. Objectives: The objectives of the study were to assess the diagnostic yield of WES in a cohort of Mexican individuals with suspected genetic eye disorders and to evaluate the improvement of diagnostic rates by reanalysis of WES data in patients without an initial molecular diagnosis. Methods: A total of 90 probands with ocular anomalies of suspected genetic origin were ascertained. Patients underwent WES in leukocytic DNA. Bioinformatics analysis and Sanger sequencing were used to confirm the disease-causing variants. Only variants identified as pathogenic or likely pathogenic were considered as causal. Results: Initial analysis revealed causal mutations in 46 cases (51%). Reanalysis of WES data 12 months after first analysis resulted in the identification of additional causal variants in 6 patients (7%), increasing the molecular diagnostic yield to 58%. The highest diagnostic rates by disease categories corresponded to hereditary retinal dystrophies (77%) and to anomalies of the anterior segment of the eye (47%). Conclusion: Our study demonstrates that WES is an effective approach for genetic diagnosis of genetic ocular diseases and that reanalysis of WES data can improve the diagnostic yield.